Steroid variability in pediatric inpatient asthmatics: survey on provider preferences of dexamethasone versus prednisone. (1st September 2020) - Cotter, Jillian M.; Tyler, Amy; Reese, Jennifer; Ziniel, Sonja; Federico, Monica J.; Anderson III, William C.; Kupfer, Oren; Szefler, Stanley J.; Kerby, Gwendolyn; Hoch, Heather E.
Abstract: Objective : Our hospital's pediatric Emergency Department (ED) began using dexamethasone for treating asthma exacerbations after ED studies showed non-inferiority of dexamethasone compared to prednisone. However, providers have not reached consensus on optimal inpatient steroid regimen. This study evaluates provider preference for inpatient steroid treatment. Methods: A survey was distributed to providers who care for inpatient pediatric asthmatics. Respondents answered questions about steroid choice and timing. Data were summarized as percentages; bivariate comparisons were analyzed with Pearson's chi-squared test. Results : Ninety-two providers completed the survey (60% response rate). When patients received dexamethasone in the ED, subsequent inpatient management was variable: 44% continued dexamethasone, 14% switched to prednisone, 2% said no additional steroids, and 40% said it depended on the scenario. Hospitalists were more likely to continue dexamethasone than pulmonologists (61% and 15%, respectively; p < .001). Factors that influenced providers to switch to prednisone in the inpatient setting included severity of exacerbation (73%) and asthma history (47%). Fifty-one percent felt uncomfortable using dexamethasone because of "minimal data to support [its] use inpatient." In case-based questions, 28% selected dexamethasone dosing intervals outside the recommended range. Thirteen percent reported experiencing errors in clinical practice. Conclusions : Use of dexamethasone in the ED for asthma exacerbations has led to uncertainty in inpatient steroid prescribing practices. Providers often revert to prednisone, especially in severe asthma exacerbations, possibly due to experience with prednisone and limited research on dexamethasone in the inpatient setting. Further research comparing the effectiveness of dexamethasone to prednisone in inpatient asthmatic children with various severities of illness is needed.